The Impact of Kazakhstan Accession to the World Trade Organization : A Quantitative Assessment - Jensen, Jesper; Tarr, David (World Bank, Washington, DC, 2012)
In this paper the authors use a computable general equilibrium model of the Kazakhstan economy to assess the impact of accession to the World Trade Organization (WTO), which encompasses (1) improved market access; (2) Kazakhstan tariff reduction; (3) reduction of barriers against entry by multinational service providers; and (4) reform of local content and value-added tax policies confronting multinational firms in the oil sector. They assume that foreign direct investment in business services is necessary for multinationals to compete well with Kazakstan business services providers, but cross-border service provision is also present. The model incorporates productivity effects in both goods and services markets endogenously, through a Dixit-Stiglitz framework. The authors estimated the ad valorem equivalent of barriers to foreign direct investment based on detailed questionnaires completed by specialized research institutes in Kazakhstan. They estimate that Kazakhstan will gain about 6.7 percent of the value of Kazakhstan consumption in the medium run from WTO accession and up to 17.5 percent in the long run. They estimate that the largest gains to Kazakhstan will derive from liberalization of barriers against multinational service providers, but the other three elements of WTO accession that the authors model all contribute positively to the estimated gains. Piecemeal sensitivity analysis shows that qualitatively the results are robust, but there are four parameters in the model that significantly affect the estimated magnitude of the gains from WTO accession.